2013
DOI: 10.3390/toxins6010020
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Levels of Deoxynivalenol, Fumonisins and Zearalenone Contaminants in Animal Feeds Used in Korea in 2012

Abstract: The objective of this study was to evaluate the occurrence and levels of deoxynivalenol (DON), fumonisins B1 and B2 (FBs), and zearalenone (ZEN) contaminants in animal feeds used in Korea in 2012. Contamination with DON was observed in 91.33% and 53.33% in compound feeds and feed ingredients, respectively. Among compound feeds, poultry layer feed (laying) exhibited the highest contaminant level of 1.492 mg/kg. FBs contaminants were present in compound feeds and feed ingredients at 93.33% and 83.33%, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…In that study, FUMs were mainly found in maize, maize silage and maize-based DDGS. In our previous study, separately performed as part of another research project with different samples in 2012 [ 44 ], the results were similar to the results of this study; most compound cattle feed was contaminated with FUMs (98%). Compound feed for early broilers was contaminated with a level of mean contamination of 3459 μg/kg and a range of 333–12,823 μg/kg.…”
Section: Discussionsupporting
confidence: 88%
“…In that study, FUMs were mainly found in maize, maize silage and maize-based DDGS. In our previous study, separately performed as part of another research project with different samples in 2012 [ 44 ], the results were similar to the results of this study; most compound cattle feed was contaminated with FUMs (98%). Compound feed for early broilers was contaminated with a level of mean contamination of 3459 μg/kg and a range of 333–12,823 μg/kg.…”
Section: Discussionsupporting
confidence: 88%
“…The mean contamination level of feed ingredients related to corn was 324 μg/kg (2009), 270 μg/kg (2010), 67 μg/kg (2012), 46 μg/kg (2014), and 20 μg/kg (2016). In our previous report in 2014 [ 12 ], which was performed separately in other research project with different samples, similar results were found in the contamination levels of the ZEN in animal feeds. Most compound feeds for cattle were contaminated with this mycotoxin, and the highest level of ZEN contamination was 405 µg/kg in cattle fatting feeds.…”
Section: Discussionsupporting
confidence: 81%
“…In Slovakia, 88% of tested poultry feed samples were contaminated with ZEN in 2004 [ 10 ]. In Asia and Oceania, Binder et al reported mean ZEN contamination level of 0.077 mg/kg in feed ingredients [ 11 ]; in Korea, ZEN was detected in 98% of tested feeds, with concentrations ranging from 0.009 to 0.405 mg/kg [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the wide number of mycotoxins, zearalonene and trichothecenes (type A mainly represented by T-2 and HT-2 toxins, and type B by deoxynivalenol (DON)) constitute one of the largest groups of mycotoxins produced by Fusarium in cereal grains [ 8 , 9 ]. Mycotoxin production in agricultural crops can occur at various stages in the food chain like pre-harvest, harvest, drying and storage.…”
Section: Introductionmentioning
confidence: 99%